Koncepcje Fryderyka Nietzschego dotyczące poszerzenia wiedzy prawnika w świetle aktualnych tendencji w prawie - Przybytek, Piotr; Przybytek, Paweł (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
In his work, the famous German philosopher Friedrich Nietzsche (1844–1900) distinguished between three types of criminals, namely: the heroic criminal, the “pale criminal,” and the degenerate criminal
Keywords: legal training; philosophy; Nietzsche, Friedrich (1844-1900); law; psychology